An automatic and accurate registration method for electro‐anatomical map and CT surface. Issue 4 (29th March 2017) - Shu, Lixia; Wang, Jin; Long, Deyong; Lin, Changyan
Abstract: Background: Electro‐anatomical maps (EAM) and CT surface registration are widely used for catheter navigation in atrial fibrillation ablations. However, few studies have investigated the registration algorithm. Moreover, some of them are semiautomatic, so that physicians must be proficient; some are inaccurate for catheter navigation. A both automatic and accurate registration method is needed. Method: A Hausdorff distance based approach (HD) was proposed for EAM/CT registration. First, using principal axes based registration, EAM/CT pairs were coarsely aligned. Then, using Hausdorff distance as the fine objective function, EAM/CT pairs were finely aligned. Results: Six real EAM/CT pairs were collected from five patients and 38 simulated pairs were generated. Each pair was aligned using Carto‐Merge, a stochastic approach (SA) and HD. Considering the balance of operability, accuracy and robustness, HD obtained the best EAM/CT registration results among the three approaches. Conclusion: Experiments validate that the proposed method registers EAM and CT surface both automatically and accurately.